2019
DOI: 10.7717/peerj.7531
|View full text |Cite
|
Sign up to set email alerts
|

Molecular taxonomy of endemic coastalLigiaisopods from the Hawaiian Islands: re-description ofL. hawaiensisand description of seven novel cryptic species

Abstract: Past phylogeographic work has shown Ligia hawaiensis, a coastal isopod species endemic to the Hawaiian Islands, to be a paraphyletic complex of several highly genetically divergent yet morphologically cryptic lineages. Despite the need for a taxonomic revision of this species, the lack of morphological differentiation has proven an impediment to formally describe new Ligia species in the region. Molecular characters and species delimitation approaches have been successfully used to formally describe cryptic sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
1
5
1
Order By: Relevance
“…The low level of diversification herein reported between individuals of T. maindroni collected at Persian Gulf locations stands in contrast with those reported for other coastal oniscid taxa (Khalaji-Pirbalouty and Raupach , 2016Raupach et al 2014;Hurtado et al 2017;Santamaria et al 2017;Greenan et al 2018;Hurtado et al 2018;Santamaria 2019), including other Tylos species (Hurtado et al 2013). For instance, the molecular characterizations of Tylos populations from the Gulf of California showed genetic differentiation in COI sequences ranging from 3.6 to 17.3%, indicating long-standing isolation of the populations in the region as well as the possible presence of cryptic species (Hurtado et al 2013).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The low level of diversification herein reported between individuals of T. maindroni collected at Persian Gulf locations stands in contrast with those reported for other coastal oniscid taxa (Khalaji-Pirbalouty and Raupach , 2016Raupach et al 2014;Hurtado et al 2017;Santamaria et al 2017;Greenan et al 2018;Hurtado et al 2018;Santamaria 2019), including other Tylos species (Hurtado et al 2013). For instance, the molecular characterizations of Tylos populations from the Gulf of California showed genetic differentiation in COI sequences ranging from 3.6 to 17.3%, indicating long-standing isolation of the populations in the region as well as the possible presence of cryptic species (Hurtado et al 2013).…”
Section: Discussioncontrasting
confidence: 99%
“…A later work by Taiti and Ferrara (1991) suggested that T. maindroni ’s geographic range extends into the Persian Gulf, including locations on the coasts of Kuwait and Iran, but additional work remains necessary to clarify the status of this species and its geographic range. Additionally, considering the high levels of genetic divergence reported in several coastal isopod taxa ( Hurtado et al 2013 ; Khalaji-Pirbalouty and Raupach 2014 , 2016 ; Raupach et al 2014 ; Hurtado et al 2017 ; Santamaria et al 2017 ; Greenan et al 2018 ; Hurtado et al 2018 ; Santamaria 2019 ), it would be important to determine if T. maindroni harbors cryptic diversity in its native range.…”
Section: Discussionmentioning
confidence: 99%
“…Khalaji‐Pirbalouty & Wägele 2010). Given our results, however, there might be huge cryptic diversity within morphologically similar and even completely identical groups, which is also suggested by other phylogenetic analyses of Ligia isopods in Hawaii (Santamaria 2019), California and Mexico (Markow & Pfeiler 2010) and East Asia (Yin et al . 2013).…”
Section: Discussionsupporting
confidence: 80%
“…Considering the previous discussed aspects, however, additional morphological and/or nuclear DNA sequence data are essential for a verification of truly distinct lineages. For freshwater and terrestrial isopods, a few studies demonstrated such integrative taxonomic approaches ( McGaughran et al 2005 ; Santamaria et al 2017 ; Santamaria 2019 ). In terms of the analyzed taxa, no previous studies discussed the existence of cryptic species, and all specimens were checked and determined carefully before molecular works started.…”
Section: Discussionmentioning
confidence: 99%